2014
DOI: 10.1074/jbc.m114.557066
|View full text |Cite
|
Sign up to set email alerts
|

Trans-activation Response (TAR) RNA-binding Protein 2 Is a Novel Modulator of Transient Receptor Potential Canonical 4 (TRPC4) Protein

Abstract: Background: The molecular composition of native TRPC4 channels is unknown. Results: Tarbp2, like Ago2 and Dicer, a protein of the RNA-induced silencing complex, binds to and functionally interacts with TRPC4. Conclusion: Upon TRPC4 binding, Tarbp2 modulates Ca 2ϩ entry and promotes Ca 2ϩ -dependent proteolytic activation of Dicer. Significance: Mechanistic insight into coupling TRPC4 activity and Dicer-dependent formation of noncoding RNAs is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Trans-activation response RNA-binding protein 2 (Tarbp2) was reported as a modulator for TRPC4 channels. Tarbp2 binding to the C terminus of TRPC4 induced the upregulation of the channel activity and increased the cytosolic Ca 2+ concentration [ 119 ]. This resulted in a dynamic regulation of Dicer, a protein requiring Ca 2+ -dependent proteolytic activation.…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…Trans-activation response RNA-binding protein 2 (Tarbp2) was reported as a modulator for TRPC4 channels. Tarbp2 binding to the C terminus of TRPC4 induced the upregulation of the channel activity and increased the cytosolic Ca 2+ concentration [ 119 ]. This resulted in a dynamic regulation of Dicer, a protein requiring Ca 2+ -dependent proteolytic activation.…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…Drosophila TRP or TRPL is about 40% identical to the TRPC1 and TRPC4. Intriguingly, the putative FKBP binding domain found in Drosophila TRPL is found in all the mammalian TRPC proteins as well [ 31 , 33 , 34 ].…”
Section: Fkbps and Critical Cellular Signalling Pathwaysmentioning
confidence: 99%
“…Moreover, many studies have further reported that TARBP2 plays an oncogenic or tumor suppressor role in many tumors, both in vitro and in vivo [10,12,13,22]. Decreased expression of TARBP2 results in miRNA decreases in human cancers [12,[29][30][31]. However, further studies are required to investigate the underlying molecular mechanisms of TARBP2 in human cancers.…”
Section: Discussionmentioning
confidence: 99%